A novel bioreactor system for biaxial mechanical loading enhances the properties of tissue-engineered human cartilage. Issue 1 (December 2017) - Meinert, Christoph; Schrobback, Karsten; Hutmacher, Dietmar; Klein, Travis
Abstract Theex vivo engineering of autologous cartilage tissues has the potential to revolutionize the clinical management of joint disorders. Yet, high manufacturing costs and variable outcomes associated with tissue-engineered implants are still limiting their application. To improve clinical outcomes and facilitate a wider use of engineered tissues, automated bioreactor systems capable of enhancing and monitoring neotissues are required. Here, we developed an innovative system capable of applying precise uni- or biaxial mechanical stimulation to developing cartilage neotissues in a tightly controlled and automated fashion. The bioreactor allows for simple control over the loading parameters with a user-friendly graphical interface and is equipped with a load cell for monitoring tissue maturation. Applying our bioreactor, we demonstrate that human articular chondrocytes encapsulated in hydrogels composed of gelatin methacryloyl (GelMA) and hyaluronic acid methacrylate (HAMA) respond to uni- and biaxial mechanical stimulation by upregulation of hyaline cartilage-specific marker genes. We further demonstrate that intermittent biaxial mechanostimulation enhances accumulation of hyaline cartilage-specific extracellular matrix. Our study underlines the stimulatory effects of mechanical loading on the biosynthetic activity of human chondrocytes in engineered constructs and the need for easy-to-use, automated bioreactor systems in cartilage tissue engineering.